Preoperative Parathyroid Needle Localization: A Minimally Invasive Novel Technique in Reoperative Settings. (13th August 2011) - Winters, Ryan; Friedlander, Paul; Noureldine, Salem; Ekaidi, Ibrahim; Moroz, Krzysztof; Kandil, Emad
Abstract : Background . Reoperative parathyroid surgery for primary hyperparathyroidism can be challenging. Numerous preoperative localization techniques have been employed to facilitate a more focused surgical exploration. This paper describes a novel, minimally invasive, and highly successful method of parathyroid localization. Methods . Patients with recurrent or persistent primary hyperparathyroidism underwent parathyroidectomy following CT scan or ultrasound-guided wire localization of the parathyroid. Accurate placement was confirmed by fine-needle aspiration with immunocytochemistry or PTH washout. The guide wire was left in situ to guide surgical excision of the gland. Curative resection was established by monitoring intact serum PTH levels after excision of the adenoma. Results . All ten patients underwent successful redo-targeted parathyroidectomy. Nine of the ten patients were discharged on the day of surgery. One patient was observed overnight due to transient postoperative hypocalcemia, which resolved with calcium supplementation. Conclusion . Placement of a localization wire via preoperative high-resolution ultrasound or CT can expedite reoperative parathyroid surgery. It allows identification of parathyroid adenoma via a minimally invasive approach, especially in cases where a sestamibi scan is inconclusive.